Beowulf : a new verse translation - Heaney, Seamus, 1939-2013 (Farrar, Straus and Giroux, 2000)
Composed toward the end of the first millennium of our era, Beowulf is the elegiac narrative of the adventures of Beowulf, a Scandinavian hero who saves the Danes from the seemingly invincible monster Grendel and, later, from Grendel's mother. He then returns to his own country and dies in old age in a vivid fight against a dragon. The poem is about encountering the monstrous, defeating it, and then having to live on in the exhausted aftermath. In the contours of this story, at once remote and uncannily familiar at the end of the twentieth century, Seamus Heaney finds a resonance that summons power to the poetry from deep beneath its surface. Drawn to what he has called the "four-squareness of the utterance" in Beowulf and its immense emotional credibility, Heaney gives these epic qualities new and convincing reality for the contemporary reader.